1995
DOI: 10.1007/bf00343926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active addition of bacterial cultures in fermented milk to patients with chronic bowel discomfort following irradiation

Abstract: Radiotherapy is a cornerstone in the treatment of malignancies in the pelvis. Consequently, there is usually exposure of the intestine and especially the lower colon and rectum, with ensuing disturbances in bowel habits at different times following radiotherapy. The main problem is diarrhoea associated with lactose intolerance, bile salt absorption and fat malabsorption. Bacterial contamination has also been described. In the present study we have evaluated the influence of the active administration of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Neither study identified significant improvements in chronic bowel symptoms in patients randomised to the intervention. In one trial (Henriksson et al, 1995), gastrointestinal symptoms improved in both groups. However, the control group Weight changes (mean and confidence interval) during pelvic radiotherapy was taking a placebo probiotic supplement containing strains thought not to be relevant for gastrointestinal symptoms.…”
Section: Complementary Nutritionmentioning
confidence: 97%
See 2 more Smart Citations
“…Neither study identified significant improvements in chronic bowel symptoms in patients randomised to the intervention. In one trial (Henriksson et al, 1995), gastrointestinal symptoms improved in both groups. However, the control group Weight changes (mean and confidence interval) during pelvic radiotherapy was taking a placebo probiotic supplement containing strains thought not to be relevant for gastrointestinal symptoms.…”
Section: Complementary Nutritionmentioning
confidence: 97%
“…Probiotic supplementation in fermented milk or sachet presentation compared to placebo (Henriksson et al, 1995;Urbancsek et al, 2001). Elemental diet (uncontrolled) (Beer et al, 1985).…”
Section: Complementary Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…As displayed in Supplementary Table S1, of the 11 studies, seven studies had no AEs caused by probiotics in prevention of chemoradiotherapy-induced diarrhea, [14][15][16][17]19,20,29 whereas four studies reported AEs with varying degrees in their treatment. 5,21,30,31 The 11 studies included 1612 people (873 consuming probiotics and 739 not consuming probiotics).…”
Section: Safety Of Probioticsmentioning
confidence: 99%
“…20) For therapeutic purposes against radiation-induced GICs, probiotics can be administered singly or as combinations of several strains selected for their antidiarrheal and anti-inflammatory effects. [3][4][5]20,22) However, the effectiveness of probiotics against GICs remains inconclusive to date. 4) A probiotic known as Kefir has become increasingly popular in recent years for its beneficial effects on human health.…”
mentioning
confidence: 99%